Illuminates : Abstract animation through projection mapping - Auzani Zeda, Mohamed Kassim (Universiti Sains Malaysia (USM), 2013)
Illuminates is a video mapping installation that explores the aesthetic of abstract animation. The animation projects and maps onto 24 pieces of white pyramids placed on the wall in a pentagonal arrangement. This project exemplifies my attempt to use technology as a tool for my artistic exploration, to express my thoughts through perceivable qualities of colours, lights, lines, shapes and motion. The animation use non-lyrical music as the storyboard flows. The inspiration for my project emerged from Khalil Gibran's quote “Trees are poems the earth writes upon the sky. We fell them down and turn them into paper, that we may record our emptiness.” The project seeks to address two elements: a harmonious feeling with nature and a sense of destruction of human eagerness in making the earth more vibrant and intense with their superficial needs. Illuminates is driven by my fascination with geometric forms and the partnership of audio and visual phenomena, all of which have often triggered the presence of beauty in my inner and the outer world. I believe the use of projection mapping technique extends its presence through physical space.